Pengaruh Penggunaan Media Film Dokumenter Terhadap Minat Belajar Sejarah Siswa Kelas XI IPS SMA Negeri 2 Sungai Raya - Tajudin, novita sari sari; Sulistyarini, Sulistyarini; Putri, Astrini Eka (Peneliti.net, 2024)
The aim of this research is to see the influence of the use of documentary film media on the interest in learning history of class XI IPS students at SMA Negeri 2 Sungai Raya. This type of research is quantitative analysis in the form of Quasi Experimental Design. There were 141 students in the study, and the sample was 71 students, where the sample was divided into two classes, namely 36 samples from the experimental group and 35 samples from the control group. In taking samples, researchers used Probality Sampling with the Cluster Sampling type. Data collection was collected through questionnaires, observation and documentation. The results of hypothesis testing using the independent t-test contain a significance value of 0.00 < 0.05. The average percentage result for the experimental group was 86.35% which was in the very high category. The response given by students was very good with an average percentage of 86.5%. The results of this research can be concluded that there is an influence of the use of documentary film media on the interest in learning history of class XI IPS students at SMA Negeri 2 Sungai Raya. Media, Documentaries, Interests